Simulation model to improve the service time at Gambang clinic - Nurul Atikah, Ramli (2014)
The aim of this research is to improve the service time in the clinic. The service time in the clinic are important and depend to number of the patient that the clinic had in a day. A simulation of a system is the operation of a model of the system. The operation of the model can be studied, properties concerning the behavior of the actual system or its subsystem that can be inferred. In its broadest sense, simulation is a tool to evaluate the performance of a system, existing proposed, under different conﬁgurations of interest and over long periods of real time. By using the simulation, the actual output is appears and it can be improved the system by using Arena software. Therefore, the important part in service time in the clinic is the queuing duration along the process in the clinic. Moreover, the Arena software can analyze the actual system and it can he modiﬁed to be more successful system. The objectives of this study are to improve the efﬁciency of the service time, to analyze system and working process, and to decrease the patient waiting duration. Furthermore, the result shows that by using Arena simulation, the service time at the clinic can be improved